Postpartum haemorrhage: clinical etiopathogenesis - Oszukowski, Przemysław; Pięta-Dolińska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2010)
Postpartum haemorrhage is the most important single cause of maternal death in both developing and developed countries. Although risk factors and preventive strategies are clearly documented, not all cases are expected or avoidable. Uterine atony is responsible for most cases and can be managed with uterine massage in conjunction with oxytocin, prostaglandins and ergot alkaloids. Retained placenta is a less common cause and requires examination of the placenta, exploration of the uterine cavity. Rarely, an invasive placenta may require surgical management. Traumatic causes include lacerations, uterine rupture and uterine inversion. Coagulopathies require clotting factor replacement for the identified deficiency. Early recognition and a multidisciplinary approach to management is most important.